A Study on the Specific Combining Ability in Several Inbred Lines of Maize - Kustanto, Heri; Hendrayana, Febri (PLANTA TROPIKA, 2023)
Maize is a cereal crop essential to fulfill the need for food and support global food security programs. Maize hybrid varieties play a very significant role in increasing maize production. Objectives of the research were to obtain a tester, which is consistent in identifying inbred lines with a high specific combining ability, and to obtain prospective crossed-hybrids that have the potential assembling to be maize hybrid varieties. The grain yield showed that the specific combining ability values ranged from -3682.2 to 5251.7. Crosses that have high and positive specific combining ability included lines of JG-11, JG-18, JG-34, JG-01, JG-40, JG-B0, JG-19, and JG-02 with a tester of JG-T00; lines of JG-20, JG-01, JG-03, JG-42, JG-02, JG-46, and tester of JG-T14; lines of JG-24, JG-08, JG-23, JG-26, JG-21, JG-07, and JG-06 with a tester of JG-T15; lines of JG-38, JG-40, JG-35, JG-36, JG-01, JG-51, JG-17, JG-B0, and JG-08 with tester of JG-T22; and lines of JG-07, JG-01, JG-26, JG-24, and JG-18 with tester of JG-T37. There were combinations of 9 crosses between inbred lines and the best testers, including JG-06XJG-T15, JG-51XJG-T22, JG-49XJG-T22, JG-B0XJG-T22, JG-35XJG-T22, JG-38XJG-T22, JG-17XJG-T22, JG-36XJG-T22, and JG-49XJG-37, which are potential as prospective maize hybrids that have high productivity.